KILL THE STEREOTYPING ON WOMEN DIRECTORSHIP: EMPIRICAL EVIDENCE FROM TOP 10 MALAYSIA COMPANIES WITH GOOD CORPORATE GOVERNANCE - Mohamad Hafiz Rosli; Farhana Hasbolah (International Journal of Accounting, Finance and Business, 2022)
Women's directorship is one of the crucial parts of business leadership. TheMalaysian Code of Corporate Governance (MCCG) 2021 states at least 30% of womendirectors. However, statistics show that women's directorship has been underrepresented onthe board of directors. Thus, this study is intended to discover the characteristics of womendirectorship among Malaysian Top 10 public listed companies with good corporate governance2020. Secondary data gathered from Company’s Annual Report 2020 and descriptive statisticsare used to present the data and discussion. The finding reveals that women director is almostwidely accepted as board members. Other characteristics such as type of directorship,education level, education field, industrial experiences, age and culture are also interrelatedwith the women directors. This finding provides insights to the policymakers, government andpublic listed companies to formulate the women policies as the board of directors and enhancesliterature.